Perbanyakan Nematoda Daun Aphelenchoides fragariae pada Biakan Cendawan : Mass Rearing of Foliar Nematode Aphlenchoides fragariae on Fungal Culture - Kurniawati, Fitrianingrum; Supramana; Hidayat, Sri Hendrastuti; Tondok, Efi Toding; Syafutra, Heriyanto (Jurnal Fitopatologi Indonesia, 2024)
Mass Rearing of Foliar Nematode Aphlenchoides fragariae on Fungal Culture This research investigated the in vitro cultivation of the foliar nematode Aphelenchoides fragariae, which can feed on both plants and fungi. As there was no prior information available in Indonesia, this study aimed to establish an efficient method for mass rearing, thereby supporting future research. Five fungal cultures i.e. Alternaria porri, Fusarium oxysporum, Botrytis cinerea, Pythium sp., and Rhizopus sp. grown in potato dextrose agar were evaluated as potential growing media at three different temperatures: 16, 28, and 37 ℃. Nematodes were surface-sterilized with streptomycin sulfat 0.1% before being introduced into the fungal cultures. Results showed that A. porri was the most favourable culture for A. fragariae reproduction, particularly at 28 ℃. Under these conditions, the average final population reached 407.8 nematodes per petri dish. Notably, A. fragariae failed to thrive at 37 ℃ in all tested fungal media. This suggests that the optimal temperature for its reproduction ranges between 16 and 28 ℃. This study provides valuable insights into the in vitro cultivation of A. fragariae, paving the way for further research utilizing this nematode species.